The efficacy of a nested polymerase chain reaction in detecting the cytochrome c oxidase subunit 1 gene of Sarcoptes scabiei var. hominis for diagnosing scabies. (1st October 2018) - Hahm, J.E.; Kim, C.W.; Kim, S.S.
Summary: Background: A widespread scabies infestation, associated with long‐term residence in nursing homes, is becoming an issue in high‐income countries. Mineral oil examination is regarded as the gold standard in diagnosing scabies, but the sensitivity of this method is generally low – approximately 50%. Molecular techniques may contribute to enhancing the sensitivity of current tests for laboratory diagnosis of human scabies. Objectives: To develop new primers for a nested polymerase chain reaction (PCR) for the cytochrome c oxidase subunit 1 ( cox1 ) gene of Sarcoptes scabiei var. hominis to increase the sensitivity of a previously developed conventional PCR. Methods: Patients with clinically suspected scabies underwent dermoscopy‐guided skin scraping with microscopic examination. The diagnosis was positive for scabies when mites or eggs were found under the microscope, and patients were then designated as 'microscopy positive'. Patients who presented with negative microscopic results were placed in the 'microscopy‐negative' group. Skin scrapings were collected from both groups for PCR. Results: Of the total 63 samples, 28 were microscopy positive and 35 were negative with no differences in sex and age between the two groups. All microscopically proven cases of scabies were positive using the cox1 nested PCR. Among microscopy‐negative samples, S. scabiei DNA was detected in nine. If sensitivity of the cox1 nested PCR is considered 100% [95% confidence interval (CI) 90·5–100], then sensitivity of microscopy is 75·7% (95% CI 58·8–88·2; P = 0·004). Conclusions: Nested PCR can be successfully used as an alternative method for diagnosing suspected scabies. Therefore, infection control measures and treatments can be initiated before significant transmission occurs, minimizing the risk of outbreaks.